The saddle gall midge, Haplodiplosis marginata (von Roser) (Diptera: Cecidomyiidae): Population dynamics and integrated management. (December 2015) - Censier, Florence; De Proft, Michel; Bodson, Bernard
Abstract: The saddle gall midge, Haplodiplosis marginata (von Roser), is a European crop pest whose larvae feed on cereal stems. Severe damage has been observed in some countries since 2010, sometimes after several decades without reports, renewing the interest of agronomists and entomologists in this sporadic pest. This review first focuses on the environmental factors influencing the life cycle of this pest and the damage it causes, as larval feeding can induce severe yield losses in the case of heavy infestation. This article also discusses the history of H. marginata outbreaks and hypotheses about its enigmatic population dynamics. This review finally presents the methods currently available to develop strategies for its integrated management. Precise monitoring of H. marginata populations appears to be an essential key to manage this pest and to understand the criteria leading to an outbreak. Highlights: Environmental factors have a major influence on the Haplodiplosis marginata life cycle. H. marginata can cause severe yield losses in the case of heavy infestation. Several sporadic outbreaks of H. marginata occurred in Europe since the 1950s. The accurate monitoring of H. marginata is one key for its integrated management.